Use of antibiotics by adults: a population-based cross-sectional study - Pereira, Jéssica Quintão; Silva, Marcus Tolentino; Galvão, Taís Freire (São Paulo Medical Journal, 2018)
BACKGROUND: The consumption of antibiotics has been widely discussed, mainly because of antibac- terial resistance, which has become a worldwide concern. In Brazil, sale of antibiotics is currently ruled by Agência Nacional de Vigilância Sanitária (ANVISA) regulation RDC 20/2011, which restricts sales to those made under medical prescription. The aims of this study were to evaluate antibiotic use and associated factors among adults in the Metropolitan Region of Manaus, Amazonas, Brazil, and to assess the propor- tion of self-medication from this use. DESIGN AND SETTING: Population-based cross-sectional study conducted in the Metropolitan Region of Manaus between May and August 2015. METHODS: Adults aged ≥ 18 years were selected through probabilistic sampling in three stages. Trained interviewers collected data from the participants in their homes. Antibiotic consumption over the last 15 days was reported. Bivariate analysis was used to calculate the prevalence ratio (PR) of antibiotic usage, with 95% confidence interval (95% CI). A multivariate model adjusted according to significant variables at P ≤ 0.20 using Poisson regression with robust variance was constructed. RESULTS: The prevalence of antibiotic use was 3.4% (95% CI 2.8-4.0%). Adjusted analysis showed that consumption was higher among women than among men (PR 1.58; 95% CI 1.11-2.24) and among people with fair health status than among those with good health (PR 1.52; 95% CI 1.08-2.15). The prevalence of self-medication was 19.0%; amoxicillin was the most self-medicated antibiotic (10/26). CONCLUSION: Antibiotic use was associated with women and individuals with fair health status. One fifth of the antibiotics were consumed through self-medication, contrary to the current Brazilian legislation.